The quality of education of the Russian political elite - N. N. Meshcheryakova; O. V. Kryshtanovskaya (Высшее образование в России)
The article examines educational strategies for the preparation of the domestic ruling class. The authors rely on two semantic concepts: “elite education” (based on the principles of selectivity and academic excellence) and “elitist” (aimed at preparing the establishment, forming social ties and securing status). The goal is to answer a series of interrelated questions. Does elite education exist in Russia? What kind of education, elite and/or elitist, is received by the administrative elite, which the state attracts to the function of management? Is the meritocratic principle of coopting new personnel into the elite realized?In the first stage of the study the authors worked with Russian and international rankings. Elite education  in  Russian  universities  was  defined  as  corresponding  to  three  criteria:  1)  qualitative  according to international experts’ assessments, 2) demanded by applicants with high final examinations  scores,  and  3)  ready  to  pay  for  it.  At  the  second  stage  the  research  was  carried  out  by  the biographical method. The data were based on the results of many years of monitoring the Russian political elite. Authors studied the biographies of 885 people who hold senior positions in the executive, legislative and judicial branches of government as of September 01, 2022.The study showed that elite education and elitist education in Russia are not one and the same. A number of universities and separate educational programs which conduct training mainly in mathematical, natural-science directions and information technologies correspond to the international approaches to quality assessment. Representatives of the elite get education in other specialties, or even in universities, which are not present in ratings. This is explained by a number of reasons: the elite is increasingly choosing legal, economic, managerial, diplomatic and military education, which Russian variants are not in demand in the world. The difference in educational trajectories between elite and elitist education also means that the fact of having higher education is important for joining the  elite,  but  not  its  quality.  The  state  does  not  purposefully  attract  graduates  of  the  best  educational programs and universities to public service. Additional factors may be important for entering the elite: capital city accommodation, participation in patron-client relations, belonging to a large corporation.Members of the elite are educated mainly in universities in the capital. The best high school graduates and the resources that families can spend on education move from the periphery to the center. But in the young generation of the elite the situation is beginning to change by increasing the number of universities they graduated from and the geography of its localization.Elite and elitist education today do not coincide, which indicates the incompleteness of the period of formation of the Russian ruling class, as well as the system of social elevators in education.